High pH reduces DNA damage caused by bile from patients with familial adenomatous polyposis: antacids may attenuate duodenal polyposis. - Scates, D K (1995)
Patients with familial adenomatous polyposis (FAP) develop periampullary duodenal tumours, suggesting that bile contributes to their formation. The hypothesis that bile contains carcinogens has been tested by looking for DNA adducts (markers of carcinogen exposure) in the duodenum of patients with or without FAP and by determining whether bile can produce DNA adducts in vitro. Using 32P-postlabelling to detect adducts, there was an excess (compared with unaffected patients) of DNA adducts in the duodenum of FAP patients and an excess of DNA adducts in the small bowel of rats treated with FAP bile, while bile from FAP patients formed significantly more DNA adducts in vitro than did bile from controls. In this study it is shown that the excess of adduct labelling produced by FAP bile in vitro depends on the pH of the incubate. While adduct labelling at pH 6-8 did not differ significantly between bile from six FAP patients and six controls, at pH 4-5 FAP bile, but not control bile, produced a near threefold excess of adduct labelling over that at pH 6-8. Therapy that increases duodenal pH may therefore alleviate duodenal polyposis.